2002
DOI: 10.1023/a:1016062117373
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The photosynthetic characteristics of four transgenic rice lines over-expressing rice NADP-malic enzyme (ME), and maize phosphoenolpyruvate carboxylase (PC), pyruvate,orthophosphate dikinase (PK), and PC+PK (CK) were investigated using outdoor-grown plants. Relative to untransformed wild-type (WT) rice, PC transgenic rice exhibited high PC activity (25-fold increase) and enhanced activity of carbonic anhydrase (more than two-fold increase), while the activity of ribulose-bisphosphate carboxylase/oxygenase (Rub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Compared to non-transformed, wild-type rice, transgenic rice expressing the maize PEPC gene required a higher light intensity to bring about photosynthesis saturation, had a higher photosynthetic CO 2 uptake rate and a higher carboxylation efficiency [33]. The PEPC substrate level (phosphoenolpyruvate) was slightly lower and the reaction product (oxaloacetate) was slightly higher in the transgenic rice, which suggested that the maize PEPC gene was functional in the transgenic rice lines [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to non-transformed, wild-type rice, transgenic rice expressing the maize PEPC gene required a higher light intensity to bring about photosynthesis saturation, had a higher photosynthetic CO 2 uptake rate and a higher carboxylation efficiency [33]. The PEPC substrate level (phosphoenolpyruvate) was slightly lower and the reaction product (oxaloacetate) was slightly higher in the transgenic rice, which suggested that the maize PEPC gene was functional in the transgenic rice lines [34].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, PEPC and PPDK transgenic rice have been reported to produce 22–24 % more grains than wild-type plants [33]. PEPC transgenic rice had higher dry weights for leaves, stems, sheaths and panicles than the untransformed wild rice, with the largest increase occurring in the panicles.…”
Section: Discussionmentioning
confidence: 99%
“…PPDK, involved in C 4 photosynthesis, was more resistant to abiotic stress and elevated CO 2 levels, ameliorating the adverse effects of induced stress. Previously, about a 5-fold increase in PPDK activity was estimated for transgenic lines compared to untransformed controls (Jiao et al, 2002). Enzymes, which are involved in C 4 carbon assimilation, are known to accumulate in leaves under different abiotic stress conditions (Fißlthaler et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The genera of Flaveria and Atriplex have been found to have multiple types of photosynthesis, such as C 3 , C 3 -C 4 and C 4 . Moreover, they can cross the species inside the genus so as to transfer C 4 photosynthetic traits into C 3 plants (Rikishi et al 1988;Jiao and Ku 1991;Jiao and Wu 1992;Jiao et al 2002). Rikishi et al (1988) obtained some C 4 -like plants derived from a cross of Atriplex rosea (C 4 )×A.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicate that PEPC transgenic rice exhibits high levels of PEPC activity, similar to that of maize (Chi et al 2001), an enhanced C 4 photosynthetic property (Chi et al 2001;Huang et al 2002), and has a higher tolerance to photooxidation compared with untransformed rice (Huang and Jiao 2001;Jiao et al , 2002Jiao et al , 2005. Using radioactive isotope methods, it has been proven that a greater amount of CO 2 is fixed in C 4 primary products, presumably indicating control of the primary CO 2 concentrating mechanism (Jiao et al 2003).…”
mentioning
confidence: 96%